Prediction Models in Veterinary and Human Epidemiology: Our Experience With Modeling Sars-CoV-2 Spread - Halasa, Tariq; Græsbøll, Kaare; Denwood, Matthew; Christensen, Lasse Engbo; Kirkeby, Carsten (Frontiers in Veterinary Science, 2020)
The worldwide outbreak of Sars-CoV-2 resulted in modelers from diverse fields being called upon to help predict the spread of the disease, resulting in many new collaborations between different institutions. We here present our experience with bringing our skills as veterinary disease modelers to bear on the field of human epidemiology, building models as tools for decision makers, and bridging the gap between the medical and veterinary fields. We describe and compare the key steps taken in modeling the Sars-CoV-2 outbreak; criteria for model choices, model structure, contact structure between individuals, transmission parameters, data availability, model validation and disease management. Finally, we address how to improve on the contingency infrastructure available for Sars-CoV-2.